LGBTQIA + HEALTH: WHAT CAN WE CONTRIBUTE? - Evelly da Silva Olanda, Débora; Fernandes Filgueiras, Mateus; de Oliveira Souza, Eclésia; Thallyta Alexandre de Pontes, Arunna; Carolina Salustino dos Santos, Maria; Claudino do Nascimento, Nathalia; Allyson Gomes Ferreira, Jefferson (Health and Society, 2022)
The health of the LBTQIA+ public deserves care and respect in a multiprofessional way, therefore, this study brought a reflection on the theme, in an integral and systematic way, from the reading of several theoretical materials. Health education seeks to improve its professionals regarding the LGBTQIA+ population, thus ensuring access to health in a humanized way, where it aims to guarantee priorities such as the eradication of discrimination in health services and improve the quality of care and services provided.